Pseudocapacitance: Emergent Pseudocapacitance of 2D Nanomaterials (Adv. Energy Mater. 13/2018). Issue 13 (4th May 2018) - Yu, Xu; Yun, Sol; Yeon, Jeong Seok; Bhattacharya, Pallab; Wang, Libin; Lee, Seung Woo; Hu, Xianluo; Park, Ho Seok
Abstract : In article number1702930, Seung Woo Lee, Xianluo Hu, Ho Seok Park and co‐workers review key aspects of emergent pseudocapacitors based on 2D nanomaterials. The history, classification, thermodynamic and kinetic aspects, and electrochemical characteristics are covered. Then design guidelines for materials, such as graphene and carbon nanosheets, transition metal oxides and hydroxides, transition metal dichalcogenides, and MXene, for extrinsically surface redox and intercalation pseudocapacitors are discussed.